How to curate content on Instagram. Taxonomy and cases - Guallar, Javier; Traver, Paula (Anuario ThinkEPI, 2023)
A taxonomy for the analysis and understanding of content curation on the Instagram platform is presented on the basis of two main dimensions, that is, content and curation, with the following categories: amount of curated content; time range of content; provenance; curation techniques; and integration of curated content. Representative cases are shown for each main format category of the social network: posts, stories, reels, and guides.
Keywords: Content curation; Digital curation; Social networks; Social media; Platforms; Instagram